Harmony of Contextualizing the Gospel and Local Theology of the Bolaang Mongondow Ethnicity - Mawikere, Marde Christian Stenly; Hura, Sudiria (Peneliti.net, 2024)
This article reviews an in-depth study on the Local Theology of the Bolaang Mongondow Ethnicity, focusing on history, ethnic origins, perspectives on God, and the contextualization efforts of the Gospel. With a long history, Bolaang Mongondow carries a cultural richness reflected in their Local Theology, examined through content analysis methods on relevant literature. Beliefs in Ompu Duata and ancestral spirits serve as the foundation of cultural authenticity, particularly in wedding and funeral customs. The worldview of this ethnic group is shaped through the elements of ancient belief in Ompu Duata. This research reveals contextualization strategies that empower Local Theology through content analysis, emphasizing the importance of preserving local terms while assigning new meanings consistent with Gospel teachings. Overall, this study provides a profound understanding of the harmonious balance between Local Theology and Gospel teachings, laying the groundwork for meaningful relationships with this ethnicity, and contributing to discussions on belief pluralism and cultural heritage preservation amid global dynamics.